Social media influencers on halal cosmetic purchase intention among Gen Z Muslims - Rokhmah, Fatma Nur; Oktari, Marina; Widiastuti, Tika (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study investigates the influence of social media influencers on the purchase intention of halal cosmetic products among Muslim Generation Z in Indonesia. This study incorporates religiosity as a moderating variable and attitude toward influencers as a mediating variable, extending the Theory of Planned Behavior (TPB) in a culturally specific context.Methodology – A quantitative approach was employed using a structured online questionnaire distributed to 308 Muslim Gen Z respondents who had been exposed to halal cosmetic content promoted by social media influencers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software.Findings – The results show that perceived credibility, trust, subjective norms, and perceived behavioral control significantly affect attitudes toward social media influencers. Attitude, in turn, had a significantly positive influence on purchase intention. However, religiosity does not significantly moderate the relationship between attitude toward influencers and purchase intention, indicating that religious commitment may not amplify or diminish the role of influencer persuasion.Implications – These findings suggest that marketers of halal cosmetics should collaborate with influencers who exhibit authenticity, trustworthiness, and alignment with Islamic values to engage Muslim Gen Z. Understanding the digital and religious sensibilities of this segment is crucial for shaping effective marketing strategies.Originality – The originality of this research lies in its specific focus on halal consumption in the cosmetics industry. Targeting Indonesian Muslim Gen Z, the study explicitly examines the role of religiosity as a moderating variable, filling a research gap on how religious values influence purchasing decisions.